Effects of laurel and myrtle extracts on the sensory, chemical and microbiological properties of vacuum‐packed and refrigerated European eel (Anguilla anguilla) fillets. (14th October 2013) - Ozogul, İlyas; Polat, Abdurrahman; Özogul, Yesim; Boga, Esmeray K.; Ozogul, Fatih; Ayas, Deniz
Summary The effects of extracted natural antioxidant (laurel and myrtle) on the sensory, chemical (TVB‐N, TBARS, PV, FFA and pH) and microbiological (total viable count, psychrotrophic bacteria and Enterbacteriaceae counts) properties of vacuum‐packaged European eel (Anguilla anguilla) stored at 4 ± 1 °C were investigated. The TBARS values of myrtle were significantly lower than that of other groups. The peroxide value was low for European eel treated with myrtle and laurel extract. The FFA‐free fatty acid concentration increased from 0.44 (% oleic acid) (2.03) in the eel during 24 days of storage. The values of pH showed statistically significant (P < 0.05) changes for all groups. The myrtle significantly reduced bacterial growth in fillets (P < 0.05). The microbiological limit of 7 log cfu per gram did not exceed in the treated groups. Data showed that the extracts of myrtle and laurel contain substances that inhibit oxidation of lipids and growth of bacteria in European eel, indicating the potential value of these extracts to extend the shelf life of fish.